2021
DOI: 10.1186/s43055-020-00396-8
|View full text |Cite
|
Sign up to set email alerts
|

Can dynamic magnetic resonance imaging replace static magnetic resonance sequences in evaluation of temporomandibular joint dysfunction?

Abstract: Background Static MRI was used as an effective tool for diagnosis of temporomandibular joint dysfunction instead of invasive techniques such as arthroscopy and arthrography. The purpose of this study was to detect whether dynamic MRI can be used instead of static MRI in diagnosis of TMJ dysfunction or not. Results According to disc displacement, anterior disc displacement was detected in 29 joints (36.25%) by both static and dynamic MRIs, and media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Magnetic resonance imaging modality was chosen for this study as it is considered the golden standard for TMJ imaging since the early 1990s by [18] then the early 2000s [19] and till 2021 it remains as the best imaging modality and the gold standard as documented by [20] . The standard MR imaging for TMJ as documented by [21] and [22] includes PD and T2-WI.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging modality was chosen for this study as it is considered the golden standard for TMJ imaging since the early 1990s by [18] then the early 2000s [19] and till 2021 it remains as the best imaging modality and the gold standard as documented by [20] . The standard MR imaging for TMJ as documented by [21] and [22] includes PD and T2-WI.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic and pseudo-dynamic TMJ MRI techniques was introduced by some researchers in 1987 [1]. According to Kamel et al, the dynamic MRI was evaluated as a contemporary diagnostic tool for examination of TMJ by comparing it to the static MRI by clinical findings and ability to diagnose various types of disc displacement, as well as for the assessment of the quality of the image by visibility of the important anatomical TMJ structures such as disc and condyle, and the presence of artifact [29]. Kamel et al concluded that dynamic MRI facilitated visualization of the articular disc during the entire pathway of jaw opening and closing as well as the dynamics of internal derangement and assessment of disc condyle relationship in a short time compared to static MRI.…”
Section: Introductionmentioning
confidence: 99%
“…The rest of the redundant images not only slow down the progress of judgment, but also sometimes mislead doctors to a certain extent [ 20 ]. In addition, considering that the diagnosis of MRI images is highly subjective and mostly depends on the experience and professional knowledge of doctors, the lack of talents in this field is also a major reason for the low efficiency of diagnoses [ 21 ]. The low recognition rate of early diagnosis leads to more difficult later-stage treatment, forming a vicious circle [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%